The sexual politics of the female body in contemporary Zimbabwean youth sociolects in interpersonal communicative contexts - Sabao, Collen (Amen-Ra Theological Seminary, 2016)
Verbal formatives describing the sexual script are often highly sexualized and gendered, perpetuating the patriarchal project. This article seeks to demonstrate how the gender politics of inequality are played in such highly sexualized everyday discourse within Zimbabwean youth sociolects. Largely viewed as apolitical and common sense, such descriptions of the sexual script are highly ideologically loaded, asserting male hegemony and ‘othering’ the female. This is achieved by conveniently appropriating applied and causative verbal extensions that deliberately and completely disregard or suppress reciprocal verbal extensions which recognise the female as an active participant to the sexual act. The paper interrogates theories and approaches in representation, (re)construction of gender identities, language and communication from Poststructural Feminist (Butler, 1990: 2004), Freudian-Lacanian psychoanalytic concerns, Saussurean linguistics approach and Bakhtinian politics of negotiated meaning (Bakhtin, 1981:1986). It is argued here that the ‘common sense’ usage of these highly gendered and sexualized verbal formatives is not politically innocent but part of the culturally/socially ingrained and institutionalized construction of gendered subjectivities. Language usage thus becomes the superstuctural semiotic tool where the appearance of subjects in ‘real life’ is embedded in these gendered cultural codes which both shape their behaviour, not apolitical and transparent, but rather how they are constructions which encode particular patriarchal views.